THE EFFECT OF BRAND AWARENESS AND GREEN MARKETING ON PURCHASE INTENTION OF PACKAGED MINERAL WATER CONSUMERS - Frans Sudirjo; Dadang Suhardi; Ratnawita Ratnawita; Kunto Atmojo; Muhammad Hery Santoso (Sean Institute, 2023)
The purpose of this study is to ascertain how brand awareness and green marketing strategies affect customer interest in purchasing bottled mineral water goods. This study uses a quantitative methodology and is a correlational investigation. Multiple linear regression analysis is used in the analytical method. The outcomes of the partial, simultaneous, and coefficient of determination tests can be used to infer the outcomes of the data analysis. The conclusion is green marketing has little impact on customers' interest in purchasing bottled water. Brand awareness significantly influences customers' desire in purchasing bottled water. In order to reach the conclusion that green marketing and brand awareness simultaneously influence consumers' purchase intentions, the significance values for green marketing and brand awareness on purchase intention are 0.000 and the calculated f value is 35.4